A review of Singapore principals' leadership qualities, styles, and roles. Issue 4 (6th July 2015) - Ng, David; Nguyen, Dong Thanh; Wong, Benjamin Koon Siak; Choy, William Kim Weng
Abstract : Purpose: – The purpose of this paper is to present a review of empirical studies on principal leadership in Singapore. It seeks to provide a general picture of Singapore principals' leadership qualities, styles, and roles. Design/methodology/approach: – This is a systematic review of empirical studies, using a "bounded" approach with a focus on the main findings of the reviewed studies. In all, 36 studies were selected for the interview. The findings of these studies were open coded, synthesized, and clustered into different themes. Findings: – The review revealed several qualities, characteristics, styles, and enacted roles of Singapore principals. While there are similarities between Singapore principals and principals elsewhere in the world, the review brought out some features unique to Singapore principals. Originality/value: – This review contributes to the growing literature in comparative research on principals' leadership and their enacted roles, and concurrently functions as a guide for further research on school leadership in Singapore.